2021
DOI: 10.7759/cureus.14605
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Pleural Mesothelioma Epidemiology in the United States From 2000 to 2016

Abstract: IntroductionPleural mesothelioma constitutes about 80% of all mesotheliomas. The peak incidence of malignant mesothelioma estimated using the cancer registries was in early 1990 to 2000 in the United States. The disease is primarily associated with asbestos exposure. The latency period between asbestos exposure and the development of malignant pleural mesothelioma (MPM) can range anywhere from 15 to 60 years. Asbestos exposure was peaked during the industrial revolution and World War II due to military and shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The incidence and mortality mesothelioma rates are consistent with trends in asbestos exposure due to the strong causal link between asbestos and mesothelioma [28]. Studies have revealed that the time of the law's implementation prohibiting the use of asbestos has an impact on these rates as well [10,[29][30][31]. MM incidence trends differ between European nations.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The incidence and mortality mesothelioma rates are consistent with trends in asbestos exposure due to the strong causal link between asbestos and mesothelioma [28]. Studies have revealed that the time of the law's implementation prohibiting the use of asbestos has an impact on these rates as well [10,[29][30][31]. MM incidence trends differ between European nations.…”
Section: Discussionmentioning
confidence: 60%
“…In Europe, pleural mesothelioma incidence rates are still rising, while certain countries have seen an overal decline [28,29]. In countries where the law banned the use of asbestos was adopted early, studies have indicated a decrease in the incidence and mortality rates of MM [10,[29][30][31]. Research that investigated nations with high cumulative asbestos consumption (> 2 million tons) between 1933 and 2012 found an overall, distinct linear correlation between the total amount of asbestos consumed and the total number of mesothelioma deaths [32].…”
Section: Introductionmentioning
confidence: 99%
“…MM is a heterogeneous tumor that includes the following three major histologic subtypes: epithelioid, sarcomatoid and biphasic. The epithelioid subtype is the most common type of mesothelioma, and it has a better prognosis than the other subtypes [ 4 ]. The median overall survival is approximately 1 year in patients with advanced surgically unresectable mesothelioma, and the 5-year overall survival (OS) is approximately 10% [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its global incidence has steadily increased, despite expectations that it would peak in 2020 1. Most cases are attributable to asbestos exposure;2 however, the latency period between exposure and development of DPM can range from 15 to 60 years and a clinical history of asbestos exposure is not always obtained 3,4. The prognosis of DPM is dismal, with reported median overall survival of only 9 to 12 months 5.…”
mentioning
confidence: 99%
“…1 Most cases are attributable to asbestos exposure; 2 however, the latency period between exposure and development of DPM can range from 15 to 60 years and a clinical history of asbestos exposure is not always obtained. 3,4 The prognosis of DPM is dismal, with reported median overall survival of only 9 to 12 months. 5 There have been minimal improvements in outcome, even in the small minority of patients eligible for surgical resection.…”
mentioning
confidence: 99%